NEUROGENIC PRURITUS IN NEUROMYELITIS OPTICA. (29th November 2012) - Elsone, L; Mutch, K; Townsend, T; Boggild, M; Nurmikko, T; Jacob, A
Abstract : Background: Pruritis (itch) is primarily a dermatologic problem. 'Neurogenic pruritus' (NP) has been described in some neurological diseases including MS and in a case with neuromyelitis optica spectrum disorder (NMOSD). Though the physiology of NP is uncertain ascending pathways or central processing could be involved. Aim: To assess the characteristics of NP in NMOSD patients. Method: Retrospective case note review followed by prospective telephone/clinic interviews of all AQP4 positive patients who attended National NMO clinic after 1 January 2011. Results: 14/45 patients reported significant pruritus during the course of NMO and were interviewed. After excluding patients with only optic neuritis or an obvious skin/systemic cause 12 (26.7%) had NP occurring within a median of 3(0–90) months from onset of NMO. The median severity on visual analogue score was 6 (2–9). In three cases pruritus developed at a median of 5 (2–28) days before onset of motor-sensory symptoms of transverse myelitis (TM); most of the remaining patients developed it within 1 month after the onset of TM. A long cervical cord lesion was seen in 9 of 12 cases and correlated well with the dermatomal distribution of NP. Conclusions: NP seems to be a common symptom associated with the TM of NMOSD.